Segmentation of Trek and Trail Race Runners as Tourists (Vallis Aurea, 2021)
This paper seeks to supplement the theory of sports marketing with additional knowledge on the participants in trek and trail races, provide basis for better understanding of their motives and behavior. The research instrument is a questionnaire consisting of 30 questions where the first part concerns with behavior at races; the second part consists of statements about the motives and the third part of descriptive questions. There were 194 participants who were interviewed by an online survey. The statistical analysis was conducted using factor analysis and cluster analysis. Five different factors / types of motivation and behavior of trek and trail race runners were extracted. Cluster analysis was also conducted and three cluster solutions were retained. Implications for marketing practice, limitations of the research and recommendations for future research were also given.